Literature Themes from Five Decades of Agricultural Communications Publications - Bo/David Williford; Leslie D. Edgar; K. Jill Rucker; Stuart Estes (Journal of Applied Communications, 2016)
The discipline of agricultural communications has been developing for nearly two centuries. As the discipline has adapted, professional organizations such as the American Association of `Agricultural College Editors (AAACE) and the Association for Communication Excellence in Agriculture, Natural Resources, and Life and Human Sciences (ACE) have published literature representative of the topics and issues that have impacted the discipline through magazines and journals such as the AAACE, ACE Quarterly, and the Journal of Applied Communications (JAC). The purpose of this study was to review the literature published in AAACE, ACE Quarterly, and JAC from 1968-2015 to identify primary and secondary literature themes. There were 13 emergent themes identified. The most prolific primary theme identified was Channel Development, Use or Research while the most prolific secondary theme identified was Educating Professionals. A count of the number of articles classified as “professional development” and “research” revealed a shift in the focus in the journal outlets. In earlier years, the discipline focused mainly on professional development articles (AAACE and ACE Quarterly), but transitioned almost completely to research (JAC). This research acknowledges that the discipline has experienced significant literary shifts and provides a recommendation for further research in audience analysis of the literature coming from the journals of the discipline.
Keywords: Agricultural Communications Literature; Content Analysis; Journal of Applied Communications Research